THE ARAB COURT OF HUMAN RIGHTS: A STUDY IN IMPOTENCE - Magliveras, Konstantinos; Naldi, Gino (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional, 2016)
An Arab human rights system remains relatively underdeveloped to this day. On September 7th 2014, the League of Arab States approved the Statute of the Arab Court of Human Rights (ACtHR) finalizing a twenty-year process to put in place a human rights mechanism resembling those operating in other regions such as Europe and the Americas. The focus of this article is on the Statute, but in view of the fact that the ACtHR’s jurisdiction is fundamentally limited to interstate cases concerning the application and interpretation of the Arab Charter on Human Rights of 2004 (2004 Charter), the 2004 Charter, revising the defunct Arab Charter on Human Rights of 1994, is briefly examined and, while progressive in parts, it is found to be imperfect in many ways. The mandate of the Arab Human Rights Committee established thereunder is looked into but its role is found to be extremely limited. The article proceeds to analyze the salient features of the Statute, which was concluded independently of the 2004 Charter, and makes comparisons with the other regional systems. The Statute is considered flawed because it confers limited powers on the ACtHR; foremost, its competence is restricted to interstate cases only, individuals have no rights of access. Taking the omission of certain judicial functions into consideration the conclusion is that the ACtHR as conceived by the Statute is unlikely to prove a forceful guardian of human rights in a troubled region.